Evaluation of an occupation-based sleep programme for people with Insomnia - Eris C. M. Ho; Andrew M. H. Siu (Hong Kong Journal of Occupational Therapy)
Background Sleep problems are a health issue worldwide. Based on the Person-Environment-Occupation-Performance model, we developed an occupation-based sleep programme to promote awareness of sleep hygiene factors, promote an environment conductive to sleep, and restructure participation in daytime activities with a focus on occupational balance. Method This study uses a non-equivalent group design to evaluate the effectiveness of an occupation-based sleep intervention among community-dwelling adults with insomnia, when compared with a treatment-as-usual (TAU) group which focused on sleep hygiene, and relaxation. Results When compared with the TAU group ( n = 20), the intervention group ( n = 22) had significant improvement in sleep duration, occupational balance, and reduction in mood symptoms at both post treatment and 1-month follow up. Conclusion The results demonstrated that an occupation-based programme is an effective treatment for insomnia disorder and demonstrated the role which occupational therapy could play in primary health care service.